Inflammation enhances IL-2 driven differentiation of cytolytic CD4 T cells. - Aspen M Workman; Ashley K Jacobs; Alexander J Vogel; Shirley Condon; Deborah M Brown (PLoS ONE)
Cytolytic CD4 T cells (CD4 CTL) have been identified in vivo in response to viral infections; however, the factors necessary for driving the cytolytic phenotype have not been fully elucidated. Our previously published work suggests IL-2 may be the master regulator of perforin-mediated cytotoxicity in CD4 effectors. To further dissect the role of IL-2 in CD4 CTL generation, T cell receptor transgenic mice deficient in the ability to produce IL-2 or the high affinity IL-2 receptor (IL-2Rα, CD25) were used. Increasing concentrations of IL-2 were necessary to drive perforin (Prf) expression and maximal cytotoxicity. Granzyme B (GrB) expression and killing correlated with STAT5 activation and CD25 expression in vitro, suggesting that signaling through the high affinity IL-2R is critical for full cytotoxicity. IL-2 signaling was also necessary in vivo for inducing the Th1 phenotype and IFN-γ expression in CD4 T cells during influenza A (IAV) infection. In addition, GrB expression, as measured by mean fluorescent intensity, was decreased in CD25 deficient cells; however, the frequency of CD4 cells expressing GrB was unchanged. Similarly, analysis of cytolytic markers such as CD107a/b and Eomesodermin indicate high IL-2Rα expression is not necessary to drive the CD4 CTL phenotype during IAV infection. Thus, inflammatory signals induced by viral infection may overcome the need for strong IL-2 signals in driving cytotoxicity in CD4 cells.